Role of Sonomammography as First Radiological Diagnostic Modality in Patients with Complain of Mastalgia - Mansoor, Mahwash; Rahman Bazai, Rizwana; Phul, Akhtar Hussain; Arifa (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate sonomammography as the first radiological diagnostic modality in patients with mastalgia. Study design: Observational cross-sectional study Place and duration of study: Department of Radiology, Sandeman Provincial Hospital Quetta and Akram Hospital Quetta from 1st February 2019 to 31st July 2019. Methodology: Ultrasounds of 60 patients were performed who presented with complain of mastalgis. Patients with history of lump, nipple discharge, carcinoma breast, implant and HRT were excluded. Result: The aged from 16 to 47 of the patients. Forty eight patients had normal/negative sonomamography. Twelve patients had positive report where lesion were, benign 9, intermediate 1 and malignant 2. There were 45 patients were married and 15 patients were unmarried. Patients with unilateral breast pain complain were 28 while bilateral were 32. Patients with cyclical breast pain were 7. Conclusion: The sonomammography is a valuable diagnostic tool in patients with breast pain to reassure and satisfy the patient. Normal ultrasound breast with proper reassurance and counseling, appropriate self examination technique can lead the way. Sonomamography is easily available at outdoor patient department. It is noninvasive and radiation free technique which is comfortably acceptable by the patient and satisfy their attendants.